2021
DOI: 10.1002/andp.202100273
|View full text |Cite
|
Sign up to set email alerts
|

Strain‐Induced Magnetism in MSi2N4 (M = V, Cr): A First‐Principles Study

Abstract: The discovery of ferromagnetic 2D van der Waals (vdW) materials has opened up opportunities for exploring and harnessing magnetism in low‐dimensional limit, and developing innovative paper‐like spintronic devices. Stress engineering demonstrates unique advantages in regulating material properties, especially for 2D materials. With the aid of first‐principles calculations, the effectiveness of strain engineering for modulating the electronic and magnetic properties of MSi2N4 (M = V, Cr) monolayers from a new fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…It is seen that the heavier the element for Z, the larger the lattice constant is, and the influence is more obvious for out-of-plane lattice c. In the VN 2 layer, each V atom is coordinated with six N atoms, forming a perfect triangular prism. The V-N bond length is 2.070 Å, slightly larger than that in VSi 2 N 4 (2.040 Å) [25], which produces different magnetic evolution under strain. In the upper and bottom outer Ge-N layer, a Ge atom coordinates to four N atoms, which leads to tetrahedron environment.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…It is seen that the heavier the element for Z, the larger the lattice constant is, and the influence is more obvious for out-of-plane lattice c. In the VN 2 layer, each V atom is coordinated with six N atoms, forming a perfect triangular prism. The V-N bond length is 2.070 Å, slightly larger than that in VSi 2 N 4 (2.040 Å) [25], which produces different magnetic evolution under strain. In the upper and bottom outer Ge-N layer, a Ge atom coordinates to four N atoms, which leads to tetrahedron environment.…”
Section: Resultsmentioning
confidence: 80%
“…Since reported, the MA 2 Z 4 (M = transition metals; A = IVA elements; Z = VA elements) family, as another milestone, has sparked a wide range of intriguing following studies. Not only the family has been enriched by predictions of new members such as MA 2 Z 4 (M = Ti, V, Cr; A = Si; Z = N, P, As), but also compositional/structural tailoring has been proposed to satisfy practical requirements [8,[18][19][20][21][22][23][24][25][26][27]. In the contribution, Zhong et al revealed that under external strain, MSi 2 N 4 (M = Ti, Cr, Mo) undergoes a phase transition which is attributed to the asymmetric charge transfer [8].…”
Section: Introductionmentioning
confidence: 99%
“…It is seen that the heavier the element for Z, the larger the lattice constant is, and the influence is more obvious for out-of-plane lattice c. In the VN 2 layer, each V atom is coordinated with six N atoms, forming a perfect triangular prism. The V-N bond length is 2.070 Å, slightly larger than that in VSi 2 N 4 ( 2.040 Å) 21 . In the upper and bottom outer Ge-N layer, a Ge atom coordinates to four N atoms, which leads to tetrahedron environment.…”
mentioning
confidence: 64%
“…Since reported, the MA 2 Z 4 (M= transition metals; A=IVA elements; Z=VA elements) family, as another milestone, has sparked a wide range of intriguing following studies. Not only the family has been enriched by predictions of new members such as MA 2 Z 4 (M=Ti, V, Cr; A=Si; Z=N, P, As), but also compositional/structural tailoring has been proposed to satisfy practical requirements 8,[16][17][18][19][20][21] . In the contribution, Zhong et al revealed that under external strain, MSi 2 N 4 (M=Ti, Cr, Mo) undergoes a phase transition which is attributed to the asymmetric charge transfer 8 .…”
mentioning
confidence: 99%
“…Depending on the space group, as well as the number of valence electrons, 1L MA 2 Z 4 can be non-magnetic or ferromagnetic semiconductors or metals, some of which exhibit topological and superconducting behavior. [7] Numerous properties of 1L MA 2 Z 4 have been predicted by DFT calculations, including robust magnetic properties, [9][10][11] defect-induced half-metalicity, [12] high piezoelectric coefficients, [13][14][15][16][17][18] ferroelectricity switchable via interlayer sliding, [19] high intrinsic lattice thermal conductivity, [20][21][22] exceptional thermoelectric performance, [23][24][25] anomalous spin and valley Hall effects, [7,9,[26][27][28] Ising superconductivity, [7] giant tunneling magnetoresistance, [29] tunable absorption coefficient, [30] and effective chemical adsorption properties. [31][32][33] Large on/off ratios were obtained in simulations of 1L MA 2 Z 4 transistors.…”
Section: Introductionmentioning
confidence: 99%